Investigating the shared genetic architecture between inflammatory bowel disease and pancreatitis: a genome-wide cross-trait analysis - Hang-Ming Qi; Ting-Ting Liu; Jia-Yun Chen; Ya-Hui Wang; Xiao-Tong Mao; Yuan-Chen Wang; Jing Jin; Xi Lin; Jianfeng Yang; Wen-Bin Zou; Le Kang; Zhuan Liao (Molecular Genetics and Genomics, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

Graphene-decorated microneedle electrode flexible array for multichannel and multimodal recording of physiological information in brain - Zhengjie Liu; Minghao Li; Xingyuan Xu; Chuanjie Yao; Jiaqi Lin; Lelun Jiang; Qiaoping Wang; Fanmao Liu; Chuanjie Zhang; Jindong Yang; Hui-jiuan Chen; Xi Xie; et al. (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Mechanistic insights into the role of nitrogen configurations driving efficient activation of low-dose ferrate (VI) for sulfonamides elimination - Zhikang Deng; Jinyao Zhu; Xi Chen; Minghui Xiang; Hui Lin; Junwei Ma; Song Cui; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Action on hot nights: A scoping review of nighttime heat thresholds and their critical role in urban climate resilience - Pixin Gong; Qi Liu; Xi Lin; Yanbing Lin; Hui Xu; Li Lan (Sustainable Cities and Society, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Photocathode-assisted desalination device based on NiO/CuInS2 heterostructure - Xing Wang; Yingchao Wang; Xi Chen; Lin Liu; Kwan San Hui; Lu Guo; Min Luo; Fuming Chen (Journal of Environmental Chemical Engineering, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Low temperature hydrochar from sewage sludge enhancing polyacrylamide-based preformed particle gels with high temperature and salinity tolerance - Bei-Bei Wu; Yan-Yan Xu; Fan Gao; Ya-Jun Wu; Lin-Hui Xi; Zhi Kang; Hong-Kui He; Zu-Guo Yang; Zhi-Xiang Xu (Journal of Water Process Engineering, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Roles of microRNAs in cardiorenal syndrome - Yilin Ren; Hui Lin; Junnan Guo; Xiaole Su; Lihua Wang; Xi Qiao (Molecular and Cellular Biochemistry, 2025)

Divergence of Two Diospyros Species Promoted by Geo‐Climatic Processes Across Dry Valleys and Lowlands in Subtropical China - Yu‐Juan Zhao; Hui‐Hui Xi; Jiao Lin; Rui Yang; Gen‐Shen Yin; Xun Gong (Journal of Biogeography, 2025)
Aim Exploring the divergence and speciation processes is central to understanding the origin and maintenance of biodiversity. The dry valley mosaic in the Hengduan Mountains and its southern extension range is one of the special landscapes globally and harbours a high level of endemic plants of tropical margin nature. The dry valleys and lowlands‐adapted plants constitute a unique system to explore how the geological and ecological effects have shaped the speciation processes here. Location Subtropical China. Taxon Diospyros dumetorum and Diospyros saxatilis. Methods We surveyed patterns of genetic variation from 33 populations spanning their distribution ranges using three chloroplast DNA fragments and eight nuclear microsatellite loci. Approximate Bayesian computation was conducted to compare population demographic models considering gene flow and to estimate key parameters. We used Ecological Niche Models (ENMs) to reconstruct changes in range distribution during glacial and interglacial periods and evaluate their niche differentiation. Results Plastid and nuclear data strongly support divergence between the two species occurring during the Pliocene/Pleistocene period followed by secondary contact in response to climatic oscillations. ENMs predicted drastic distribution range changes during the Quaternary and identified significant differences in climatic conditions at the set of locations occupied by these two species. Correlation analyses were conducted, and the results suggest that geographical isolation rather than environmental heterogeneity shapes the current population genetic structure within the two species. Main Conclusion Phylogeographical patterns revealed in our results document that geographic vicariance associated with tectonic uplifts initiated allopatric species divergence between the two dry valleys and lowlands‐adapted Diospyros species, and niche differentiation perhaps further accelerated the speciation processes with limited subsequent gene flow. Our findings could contribute to the knowledge of forces that drive speciation processes in the unique landscape of dry valleys, as well as the evolution of the flora in subtropical China.

Robust titanium suboxide anodes doped by sintering enhance PFOS degradation in water - Yufei Sui; Xi Zhu; Lei Li; Yaye Wang; Gengyang Li; Shuping Dong; Yifei Wang; Hui Lin; Ke Li; Qingguo Huang (Chemosphere, 2025)

Five racemic phthalides from the aerial parts of Lycopodiastrum casuarinoides and their neuroprotective activities - Yang Liu; Xi Chen; Xue-Jin Liu; Ren Liu; Hui-Ling Hu; Shan-Xue Min; Chao-Hui Huang; Lin Liu; Gui-Shan Tan (Phytochemistry, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

How bedding-parallel fractures affect fluid activity in a relatively closed lacustrine shales system: Evidence from calcite veins - Zilong Li; Kelai Xi; Xiaobing Niu; Xiujuan Wang; Wenzhong Ma; Xiao Hui; Jiangyan Liu; Changyu Fan; Miruo Lin; Keyu Liu; Yingchang Cao (Marine and Petroleum Geology, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Influence of rhizospheric symbiotic microorganisms on the behavioural effects of antimony in soil-plant system: Insights from a proteomic perspective - Min Zhou; Hui Li; Lin Xi; Feng Shi; Xinru Li; Fanfan Wang; Xuesong Liu; Hailei Su; Yuan Wei (Journal of Hazardous Materials, 2024)

Interactions between microplastics and heavy metals in leachate: Implications for landfill stabilization process - Jiabao Chen; Lin Huo; Ying Yuan; Yu Jiang; Hui Wang; Kunlong Hui; Yanjiao Li; Zekai Huang; Beidou Xi (Journal of Hazardous Materials, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Delaying cyclization of polyacrylonitrile by boric acid for sulfurized poly(acrylonitrile) cathode materials - Xuan Zhang; Hui-Chao Lu; Chen-Ran Hao; Ji-Qiong Liu; Xi-Rui Kong; Jiu-Lin Wang (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Selective catalytic oxidation of DMF over Cu-Ce/H-MOR by modulating the surface active sites - Hua-Hui Xu; Yi-Wei Xian; Xi Zhao; Lin-Ya Xu; Cai-Hao Wen; Han Zhao; Cen Tang; Wen-Zhi Jia; Meng-Fei Luo; Jian Chen (Journal of Hazardous Materials, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

A novel approach for sludge deep-dewatering via flowing-out enhancement but not relying on cell lysis and bound water release - Hao Zhang; Wen-Hui Liu; Yun-Yan Gao; Ping Sun; Yuan-Ping Zeng; Lin-Lin Ma; Jiang-Nan Wu; Shun-Gui Zhou; Xi-Qin Cui; Raymond Jianxiong Zeng; Hou-Feng Wang (Water Research, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

Cytotoxic flavonoids from the leaves of Callicarpa nudiflora hook - Jin-Lin Zhang; Yin Xiao; Lu Zhou; Shao-Yang Yin; Jia-Yin Long; Hong-Lin Xiang; Xi-Feng Sheng; Hui Zou (Natural Product Research, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Association between blood arsenic concentration and dyslipidemia: Mediating effect of lipid peroxidation in the elderly - Jia-Hui Huang; Yi Wu; Wei He; Jun-Xian Wang; Lin Fu; Xi Chen (Journal of Trace Elements in Medicine and Biology, 2024)

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Umbelliferon: a review of its pharmacology, toxicity and pharmacokinetics - Zhi Lin; Xi Cheng; Hui Zheng (Inflammopharmacology, 2023)

Mixed exposure effect of seminal metals on semen quality, mediation of total antioxidant capacity, and moderation of GSTM1/GSTT1 gene deletion in Chinese reproductive-aged men - Jingchao Ren; Huidong Jin; Chen Zhang; Song Liu; Yufen Han; Jinyan Xi; Jinhu Cao; Fenglong Lin; Pingyang Zhang; Fengquan Zhang; Guang-hui Zhang; Huijun Yang; et al. (Environmental Research, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

A novel l-rhamnose-binding lectin participates in defending against bacterial infection in zebrafish - Jing Wang; Xin-Lu Guo; Hong-Ye Chen; Lin-Xi Xiao; Gui-Wen Yang; Hui-Ting Yang (Fish & Shellfish Immunology, 2023)

Cobalt exposure and dyslipidemia in elderly population: the mediating role of systemic inflammation and lipid peroxidation - Jia-Hui Huang; Li Tao; Yi Wu; Wei He; Jun-Xian Wang; Xi Chen; Lin Fu (Environmental Science and Pollution Research, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Detection and genetic analysis of porcine circovirus-like virus in pigs with diarrhea between 2016 and 2021 in Henan and Shanxi provinces of China - Liu-Hui Zhang; Lin-Qing Wang; Hong-Xuan Li; Hong-Lei Zhang; Lan-Lan Zheng; Xi-Meng Chen; Hong-Ying Chen (Archives of Virology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Vanadium isotope evidence for widespread marine oxygenation from the late Ediacaran to early Cambrian - Wei Wei; Xi Chen; Hong-Fei Ling; Fei Wu; Lin-Hui Dong; Songqi Pan; Zhenhua Jing; Fang Huang (Earth and Planetary Science Letters, 2023)

Regulation of enzymatic and non-enzymatic antioxidants in rice seedlings against chromium stress through sodium hydrosulfide and sodium nitroprusside - Yu-Juan Lin; Xing-Hui Feng; Yu-Xi Feng (Environmental Science and Pollution Research, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Changes in the growth performance, antioxidant enzymes and stress resistance caused by dietary administration of synbiotic (fructooligosaccharide and probiotics) in juvenile Chinese Mitten Crab, Eriocheir sinensis - Jin-Juan Wan; Jian-lin Pan; Mei-Fang Shen; Hui Xue; Meng-lin Sun; Mei-Qin Zhang; Xi-He Zhu; Xing-kong Ma (Aquaculture International, 2022)

Climate warming promotes deterministic assembly of arbuscular mycorrhizal fungal communities - Xinyu Xu; Yunpeng Qiu; Kangcheng Zhang; Fei Yang; Mengfei Chen; Xi Luo; Xuebin Yan; Peng Wang; Yi Zhang; Huaihai Chen; Hui Guo; Lin Jiang; et al. (Global Change Biology, 2022)
Arbuscular mycorrhizal fungi (AMF) significantly contribute to plant resource acquisition and play important roles in mediating plant interactions and soil carbon (C) dynamics. However, it remains unclear how AMF communities respond to climate change. We assessed impacts of warming and precipitation alterations (30% increase or decrease) on soil AMF communities, and examined major ecological processes shaping the AMF community assemblage in a Tibetan alpine meadow. Our results showed that warming significantly increased root biomass, and available nitrogen (N) and phosphorus (P) in soil. While precipitation alterations increased AMF abundances, they did not significantly affect the composition or diversity of AMF communities. In contrast, warming altered the composition of AMF communities and reduced their Shannon–Wiener index and Pielou's evenness. In particular, warming shifted the AMF community composition in favor of Diversisporaceae over Glomeraceae, likely through its impact on soil N and P availability. In addition, AMF communities were phylogenetically random in the unwarmed control but clustered in warming plots, implying more deterministic community assembly under climate warming. Warming enhancement of root growth, N and P availability likely reduced plant C‐allocation to AMF, imposing stronger environmental filtering on AMF communities. We further proposed a conceptual framework that integrates biological and geochemical processes into a mechanistic understanding of warming and precipitation changes’ effects on AMF. Taken together, these results suggest that soil AMF communities may be more sensitive to warming than expected, highlighting the need to monitor their community structure and associated functional consequences on plant communities and soil C dynamics under the future warmer climate.

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Improving the observation and prediction capabilities for Arctic marine environment: from the perspective of Arctic Shipping - Hui Wang; Qizhen Sun; Lin Zhang; Xi Liang; Qinghua Yang; Na Liu; Chunhua Li; Qingsheng Liu; Bingrui Li; Qian Feng; Xiao Cheng; Yi Yu (Acta Oceanologica Sinica, 2021)

Beyond resource limitation: an expanded test of the niche dimension hypothesis for multiple types of niche axes - Xuebin Yan; Jeffrey Diez; Kailing Huang; Shaopeng Li; Xi Luo; Xinyu Xu; Fanglong Su; Lin Jiang; Hui Guo; Shuijin Hu (Oecologia, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

Tobacco alpha-expansin EXPA4 plays a role in Nicotiana benthamiana defence against Tobacco mosaic virus - Li-Juan Chen; Wen-Shan Zou; Guo Wu; Hong-Hui Lin; De-Hui Xi (Planta, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Rice false smut fungus hijacks the rice nutrients supply by blocking and mimicking the fertilization of rice ovary - Jie‐Hui Song; Wei Wei; Bo Lv; Yang Lin; Wei‐Xiao Yin; You‐Liang Peng; Guido Schnabel; Jun‐Bin Huang; Dao‐Hong Jiang; Chao‐Xi Luo (Environmental Microbiology, 2016)
Summary Rice false smut disease is an increasing threat to rice production in the world. Despite of best efforts, research for the infection of the fungus has yielded equivocal and conflicting results about where and how the infection is initiated and developed. Here we show a stepwise infection pattern and sophisticated regulation during this process. Initial infection occurred on the filaments, which prevented the production of mature pollen thus blocked the pollination. In the following days, the pathogen invaded the stigmas and styles, occasionally the ovaries. Expression analysis indicated that the fungus mimicked a successful fertilization process and enabled the continuous supply of nutrients for fungus to produce false smut balls. The stepwise infection of flower organs and mimicry of ovary fertilization unveiled in this study guided the rice plant into supplying nutrients for false smut ball development and represents a new and unique biological process of host pathogen interactions.

Isolation, diversity and acetylcholinesterase inhibitory activity of the culturable endophytic fungi harboured in Huperzia serrata from Jinggang Mountain, China - Ya Wang; Zheng Lai; Xi-Xi Li; Ri-Ming Yan; Zhi-Bin Zhang; Hui-Lin Yang; Du Zhu (World Journal of Microbiology and Biotechnology, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Characterisation of the dark green islands of cucumber mosaic virus infected Nicotiana tabacum - Li-Juan Chen; Jian Liu; Fei-Fei Zhao; Jing-Yi Li; Sheng-Xuan Wang; Hong-Hui Lin; De-Hui Xi (Plant Cell Reports, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

The Chilli Veinal Mottle Virus Regulates Expression of the Tobacco Mosaic Virus Resistance Gene N and Jasmonic Acid/Ethylene Signaling Is Essential for Systemic Resistance Against Chilli Veinal Mottle Virus in Tobacco - Feng Zhu; De-Hui Xi; Xing-Guang Deng; Xing-Ji Peng; He Tang; Ying-Juan Chen; Wei Jian; Hong Feng; Hong-Hui Lin (Plant Molecular Biology Reporter, 2014)

Recombinant expression and functional analysis of a Chlamydomonas reinhardtii bacterial-type phosphoenolpyruvate carboxylase gene fragment - Qi-Lin Tian; Ding-Ji Shi; Xiao-Hui Jia; Hua-Ling Mi; Xi-Wen Huang; Pei-Min He (Biotechnology Letters, 2014)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

Mechanism of BDE209-induced impaired glucose homeostasis based on gene microarray analysis of adult rat liver - Zhan Zhang; Zhen-Zhen Sun; Xue Xiao; Shixin Zhou; Xi-Chen Wang; Jun Gu; Liang-Lin Qiu; Xu-Hui Zhang; Qiujin Xu; Binghui Zhen; Xinru Wang; Shou-Lin Wang (Archives of Toxicology, 2013)

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

Isolation and characterization of microsatellite loci in the Reevese’s butterfly lizard Leiolepis reevesii (Agamidae) - Lei Hua; Lu-Xi Mao; Ce Chen; Jian-Fang Gao; Long-Hui Lin (Conservation Genetics Resources, 2012)

New epothilone congeners from Sorangium cellulosum strain So0157-2 - Ji-Dong Wang; Nan Jiang; Hui Zhang; Lin-Ping Ying; Chuan-Xi Wang; Wen-Sheng Xiang; Bo Wu; Hai-Bin Wang; Hua Bai (Natural Product Research, 2011)

The roles of ascorbic acid and glutathione in symptom alleviation to SA-deficient plants infected with RNA viruses - Shao-Dong Wang; Feng Zhu; Shu Yuan; Hui Yang; Fei Xu; Jing Shang; Mo-Yun Xu; Shu-Dan Jia; Zhong-Wei Zhang; Jian-Hui Wang; De-Hui Xi; Hong-Hui Lin (Planta, 2011)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

A broad-spectrum, efficient and nontransgenic approach to control plant viruses by application of salicylic acid and jasmonic acid - Jing Shang; De-Hui Xi; Fei Xu; Shao-Dong Wang; Sen Cao; Mo-Yun Xu; Ping-Ping Zhao; Jian-Hui Wang; Shu-Dan Jia; Zhong-Wei Zhang; Shu Yuan; Hong-Hui Lin (Planta, 2011)

Characterization of a male sterile mutant from progeny of a transgenic plant containing a leaf senescence-inhibition gene in wheat - Ya-Jun Xi; Xue-Feng Ma; Huan Zhong; Shu-Dong Liu; Zhu-Lin Wang; Yang-Yang Song; Cheng-Hui Zhao (Euphytica, 2011)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

BAK1 and BKK1 in Arabidopsis thaliana confer reduced susceptibility to turnip crinkle virus - Hui Yang; Xiaoping Gou; Kai He; Dehui Xi; Junbo Du; Honghui Lin; Jia Li (European Journal of Plant Pathology, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

shRNA-targeted Cyclooxygenase (COX)-2 inhibits proliferation, reduces invasion and enhances chemosensitivity in laryngeal carcinoma cells - Rui Wang; Xi Wang; Fang Lin; Ping Gao; Ke Dong; Hui-Zhong Zhang (Molecular and Cellular Biochemistry, 2008)

Biological and ecological features of saline lakes in northern Tibet, China - Zhao Wen; Zheng Mian-ping; Xu Xian-zhong; Liu Xi-Fang; Guo Gan-lin; He Zhi-hui (Hydrobiologia, 2005)